1998
DOI: 10.1093/molehr/4.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Ooplasmic transfer in mature human oocytes

Abstract: Ooplasmic transplantation aimed at restoring normal growth in developmentally compromised oocytes and embryos was evaluated in seven couples (eight cycles) with multiple implantation failures. Two approaches were investigated to transfer ooplasm from donor eggs at metaphase II (MII) stage into patient MII eggs: (i) electrofusion of a ooplasmic donor fragment into each patient egg (three cycles), and (ii) direct injection of a small amount of ooplasm from a donor egg into each patient egg (five cycles). Some do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
198
0
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(209 citation statements)
references
References 44 publications
4
198
0
7
Order By: Relevance
“…Fully mature cytoplasm of the oocyte provides the embryo with a battery of maternal mRNAs, proteins, and mitochondria, which are related to oocyte development competence and which may contribute to apoptotic pathways but also to defense mechanisms against apoptosis (Fair et al 1995, Otoi et al 1997, Stojkovic et al 2001. Microinjection of healthy cytoplasm protected oxidative-stressed zygotes from apoptotic death in mice (Liu & Keefe 2000) and improved fertility in older patients with compromised embryos in humans (Cohen et al 1998, Barritt et al 2001. Porcine studies have also shown that mitochondrial activity increases during meiotic progression and cumulus expansion (Thorner et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Fully mature cytoplasm of the oocyte provides the embryo with a battery of maternal mRNAs, proteins, and mitochondria, which are related to oocyte development competence and which may contribute to apoptotic pathways but also to defense mechanisms against apoptosis (Fair et al 1995, Otoi et al 1997, Stojkovic et al 2001. Microinjection of healthy cytoplasm protected oxidative-stressed zygotes from apoptotic death in mice (Liu & Keefe 2000) and improved fertility in older patients with compromised embryos in humans (Cohen et al 1998, Barritt et al 2001. Porcine studies have also shown that mitochondrial activity increases during meiotic progression and cumulus expansion (Thorner et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress can also influence the oocyte spindle assembly (Tarín, 1996), because oxidative stress may trigger mPT pore opening and decrease ATP content in oocytes (Zhang et al, 2006). It is therefore not surprising that injection of cytoplasm may improve embryo quality and support the embryo development (Cohen et al, 1998).…”
Section: Mitochondria and Meiosis In Oocytesmentioning
confidence: 99%
“…Many studies were performed in order to ascertain factors that af-fect the fertilization rate, where the fertilization rate and embryo quality have been described in conjunction with polar body orientation or meiotic spindle position. The M-II spindle is located at the periphery of the ooplasm, subjacent to the first polar body (2). Therefore, during the ICSI procedure sperm injection at the M-II spindle area should be avoided, and a six or twelve o'clock position in relation to the polar body chosen (3,4).…”
Section: Introductionmentioning
confidence: 99%